2021
DOI: 10.1111/ijcp.14962
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between CRP at admission and thorax CT findings in patients diagnosed with COVID‐19

Abstract: Introduction The current study aims to evaluate the relationship between C‐reactive protein (CRP) levels, thorax CT findings and CT‐SS in patients presenting to the emergency department with COVID‐19. Methods Patients diagnosed with COVID‐19 by nasopharyngeal rt‐PCR (+) in the emergency department were included in the study. In addition to the CRP, ferritin and D‐dimer examinations of patients at admission, thorax CT involvement findings and CT‐SS results were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Moreover, in a study conducted by Tan et.al, correlation analysis showed that CRP (R = 0.62; p < 0.001) was positively correlated with CT scores [ 22 ], as in our study where CRP positively correlates with CT changes (R = 0.40; p < 0.001). In similarity with our findings, several studies found that CRP levels correlate with lung lesion at CT scan and disease severity [ 6 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in a study conducted by Tan et.al, correlation analysis showed that CRP (R = 0.62; p < 0.001) was positively correlated with CT scores [ 22 ], as in our study where CRP positively correlates with CT changes (R = 0.40; p < 0.001). In similarity with our findings, several studies found that CRP levels correlate with lung lesion at CT scan and disease severity [ 6 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, for patients with cardiovascular disease, CRP levels positively correlated with AST, ALT, LDH, IL6 and fibrinogen. Similarly to other studies which reported a positive correlation between the severity of thorax CT (quantitative CT scores), our results also revealed a correlation between CRP levels and CT results [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The meta-analysis noted that combining HM therapy decreases CRP significantly, but does not decrease Il-6, indicating that HM helps to reduce the inflammatory status through an uncertain pathway. In a previous study, the CRP level correlated with the severity of lung involvement and prognosis (Beydogan and Yuruk Atasoy, 2021). In this context, it makes sense that many Chinese herbal medicines utilized in these trials targeted the lung meridian and anti-inflammatory effects are especially valuable.…”
Section: Discussionmentioning
confidence: 93%